Basic mechanism of the autonomous ClpG disaggregase - Katikaridis, Panagiotis; Römling, Ute; Mogk, Axel (The journal of biological chemistry, 2021)
Bacterial survival during lethal heat stress relies on the cellular ability to reactivate aggregated proteins. This activity is typically executed by the canonical 70-kDa heat shock protein (Hsp70)-ClpB bichaperone disaggregase, which is most widespread in bacteria. The ClpB disaggregase is a member of the ATPase associated with diverse cellular activities protein family and exhibits an ATP-driven threading activity. Substrate binding and stimulation of ATP hydrolysis depends on the Hsp70 partner, which initiates the disaggregation reaction. Recently elevated heat resistance in gamma-proteobacterial species was shown to be mediated by the ATPase associated with diverse cellular activities protein ClpG as an alternative disaggregase. Pseudomonas aeruginosa ClpG functions autonomously and does not cooperate with Hsp70 for substrate binding, enhanced ATPase activity, and disaggregation. With the underlying molecular basis largely unknown, the fundamental differences in ClpG- and ClpB-dependent disaggregation are reflected by the presence of sequence alterations and additional ClpG-specific domains. By analyzing the effects of mutants lacking ClpG-specific domains and harboring mutations in conserved motifs implicated in ATP hydrolysis and substrate threading, we show that the N-terminal, ClpG-specific N1 domain generally mediates protein aggregate binding as the molecular basis of autonomous disaggregation activity. Peptide substrate binding strongly stimulates ClpG ATPase activity by overriding repression by the N-terminal N1 and N2 domains. High ATPase activity requires two functional nucleotide binding domains and drives substrate threading which ultimately extracts polypeptides from the aggregate. ClpG ATPase and disaggregation activity is thereby directly controlled by substrate availability.
Gesehen am 22.10.2021